A low cost solution for post-biopsy complications using available RFA generator and coaxial core biopsy needle - Azlan, C. A.; Nasrul Fazli, Mohd Nasir; Ahmad Saifizul, Abdullah; Faizul, M.S.; Ng, K.H.; Abdullah, B.J.J. (Australia College of Physical Scientists and Engineers in Medicine (ACPSEM), 2009)
Link to publisher's homepage at http://www.acpsem.org.au/